2019
DOI: 10.1371/journal.pone.0210991
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with multidrug resistant organisms determines the clinical course of patients with acute myeloid leukemia undergoing intensive induction chemotherapy

Abstract: IntroductionThe global spread of multidrug-resistant organisms (MDRO) complicates treatment and isolation measures in hospitals and has shown to increase mortality. Patients with disease- or therapy-related immunodeficiency are especially at risk for fatal infections caused by MDRO. The impact of MDRO colonization on the clinical course of AML patients undergoing intensive induction chemotherapy—a potentially curative but highly toxic treatment option—has not been systematically studied.Materials & methods312 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…In order to identify the occurrence of CR in HM patients and to understand its epidemiology, we reviewed series and selected case reports that report colonization or infection of HM patients with CR bacteria. These studies were undertaken in different areas of the world, including New York, New Delhi, China, Stockholm, Frankfurt, Roma, Brescia, Athens, Ankara, Cairo, and Haifa in the series studies ( Tables 1 −3; Cattaneo et al, 2012 , 2018 ; Kjellander et al, 2012 ; Schelenz et al, 2013 ; Satlin et al, 2013a , 2016 ; El-Mahallawy et al, 2014 ; Trecarichi et al, 2015 , 2016 ; Wang et al, 2015 , 2017 ; Micozzi et al, 2017 ; Ballo et al, 2019 ), and in United States, Brazil, Spain, Italy, Poland, Turkey, Israel, Japan, China, and Austria in the case reports ( Table 4 ; Muchtar et al, 2012 ; Carattoli et al, 2013 ; Chang et al, 2013 ; Satlin et al, 2013b ; Girmenia et al, 2015 ; Huang et al, 2015 ; Kara et al, 2015 ; Leitner et al, 2015 ; Xing et al, 2015 ; Kantarcioglu et al, 2016 ; Tofas et al, 2016 ; Zhang et al, 2016 , 2018 ; Majewski et al, 2017 ; Piedra-Carrasco et al, 2017 ; Asai et al, 2018 ). When we geolocate the regions that have reported the presence of CR bacteria in HM patients in Figure 1 , it can be observed that all these studies have been reported in regions that are either endemic or have a significant increase in carbapenemase enzymes (a coincidence with regions with high levels of CR bacteria) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to identify the occurrence of CR in HM patients and to understand its epidemiology, we reviewed series and selected case reports that report colonization or infection of HM patients with CR bacteria. These studies were undertaken in different areas of the world, including New York, New Delhi, China, Stockholm, Frankfurt, Roma, Brescia, Athens, Ankara, Cairo, and Haifa in the series studies ( Tables 1 −3; Cattaneo et al, 2012 , 2018 ; Kjellander et al, 2012 ; Schelenz et al, 2013 ; Satlin et al, 2013a , 2016 ; El-Mahallawy et al, 2014 ; Trecarichi et al, 2015 , 2016 ; Wang et al, 2015 , 2017 ; Micozzi et al, 2017 ; Ballo et al, 2019 ), and in United States, Brazil, Spain, Italy, Poland, Turkey, Israel, Japan, China, and Austria in the case reports ( Table 4 ; Muchtar et al, 2012 ; Carattoli et al, 2013 ; Chang et al, 2013 ; Satlin et al, 2013b ; Girmenia et al, 2015 ; Huang et al, 2015 ; Kara et al, 2015 ; Leitner et al, 2015 ; Xing et al, 2015 ; Kantarcioglu et al, 2016 ; Tofas et al, 2016 ; Zhang et al, 2016 , 2018 ; Majewski et al, 2017 ; Piedra-Carrasco et al, 2017 ; Asai et al, 2018 ). When we geolocate the regions that have reported the presence of CR bacteria in HM patients in Figure 1 , it can be observed that all these studies have been reported in regions that are either endemic or have a significant increase in carbapenemase enzymes (a coincidence with regions with high levels of CR bacteria) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, in a review of studies published worldwide before 2012, Falagas et al (2014) estimated that 26 to 44% of deaths worldwide were due to CR (Falagas et al, 2014), and Borer et al (2009) reported the highest attributable mortality rate for CR-K. pneumoniae bacteremia in all comorbidities as 50% with a mortality risk ratio of 3.3 (95% CI, 2.9-28.5) (Borer et al, 2009). Moreover, in a carbapenemase non-endemic European country, CR-colonized HM patients had a significantly reduced 60-and 90-day, as well as 1-and 2-year survival rates when compared to non-colonized patients (Ballo et al, 2019).…”
Section: Factors Of Mortality In Hm Patients With Cr Bacterial Infectmentioning
confidence: 99%
See 2 more Smart Citations
“…The other side of the coin is the threat of multidrug resistance, which has even been reported to influence the clinical course of AML. 41,42 Pseudomonas aeruginosa is still relatively sensitive to fluoroquinolones in Finland 43 suggesting possibility to consider prophylaxis.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%